2016
DOI: 10.1200/jco.2016.34.4_suppl.tps182
|View full text |Cite
|
Sign up to set email alerts
|

A study of the combination of oxaliplatin, capecitabine, and herceptin (trastuzumab) and chemoradiotherapy in the adjuvant setting in operated patients with HER2+ gastric or gastro-esophageal junction cancer (TOXAG study).

Abstract: TPS182 Background: Trastuzumab in combination with chemotherapy has been shown to prolong survival of HER2+ esophago-gastric cancer patients. The primary aim of our study was to evaluate safety and tolerability of trastuzumab (T) in combination with oxaliplatine (O), capecitabine (C) and radiation (R) therapy in the adjuvant setting in curatively resected esophago-gastric cancer patients. Methods: Forty patients with IB or higher stages was planned to be recruited and here we report the interim analyses on 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The overexpression of human epidermal growth factor receptor 2 (HER2, c‐erbB2) is found in up to 30% of breast cancers; in addition, compared to patients with HER2‐negative breast cancer, patients with HER2‐positive breast cancer were associated with significantly worse outcomes 51 . Many studies have demonstrated that HER2 is also present in other cancers, particularly in gastric cancer 52‐55 . Trastuzumab is a critical drug for the treatment of HER2‐positive breast cancer that also has been shown to be useful for the treatment of HER2‐positive gastric cancer 56 ; it is approved by the European Union, the United States, and China for the treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of human epidermal growth factor receptor 2 (HER2, c‐erbB2) is found in up to 30% of breast cancers; in addition, compared to patients with HER2‐negative breast cancer, patients with HER2‐positive breast cancer were associated with significantly worse outcomes 51 . Many studies have demonstrated that HER2 is also present in other cancers, particularly in gastric cancer 52‐55 . Trastuzumab is a critical drug for the treatment of HER2‐positive breast cancer that also has been shown to be useful for the treatment of HER2‐positive gastric cancer 56 ; it is approved by the European Union, the United States, and China for the treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…51 Many studies have demonstrated that HER2 is also present in other cancers, particularly in gastric cancer. [52][53][54][55] Trastuzumab is a critical drug for the treatment of HER2-positive breast cancer that also has been shown to be useful for the treatment of HER2-positive gastric cancer 56 ; it is approved by the European Union, the United States, and China for the treatment of gastric cancer. Currently, there is no report comparing the exhaled metabolomics of these two types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the TOXAG study showed that adding trastuzumab to adjuvant radio chemotherapy is tolerable in terms of toxicity, though we currently lack data on its effectiveness [23].…”
Section: Discussionmentioning
confidence: 99%
“…By pre-de ning an α = 0.10 and β = 0.64, xed comparisons would be carried out by Fisher's Exact test. If the prede ned α value is signi cantly better than the tolerability percentage of 64.0% observed in INT0116, we would continue to recruit more patients up to 40, which was ultimately the responsibility of the Independent Data and Safety Monitoring Committee, which was presented previously [13].…”
Section: Interim Analysismentioning
confidence: 99%